Letter of request for compensation to Monica Doblado for service of her estranged husband ([Publisher not identified], 1828)
This is a formal petition letter by Monica Doblado requesting compensation for service of her estranged husband Rafael Campoverde who was executed by the division of Negrete during the Mexican war of independence in 1810.